Impact of polyethylene terephthalate on the mechanical properties of polyimide films - Yar-Mukhamedova, G.Sh.; Muradov, A.D.; Mukashev, K.; Umarov, F.; Imanbayeva, A.K.; Mussabek, G.K.; Belisarova, F. (Karagandy University of the name of acad. E.A. Buketov, 2025)
This study focuses on analyzing the influence of varying concentrations of polyethylene terephthalate filler on both the tensile strength and elongation at break properties of polyimide films when subjected to uniaxial tension, aiming to determine how polyethylene terephthalate filler impacts the mechanical performance and durability of these films under stress. The mechanical behavior of polyimide films and their homogeneous composites with polyethylene terephthalate under uniaxial tension were investigated. The samples were prepared by mechanically mixing polyimide varnish solutions with polyethylene terephthalate, which serves as a reinforcing filler. The results demonstrate that, for all sample types, an initial mechanical load until induces a sharp ~3% increase in relative elongation, attributed to the rotation of globules and alignment of matrix macromolecules into extended chains along the load direction. The additive dependence of viscosity observed in the study further supports that no chemical bonds are formed between the polyimide and polyethylene terephthalate macromolecules, and that no conformational changes take place within the composite.
Keywords: polyimide; polyethylene terephthalate; filler; uniaxial tension; IR spectroscopy; viscometry